Effectiveness of Implementation of Government Accounting Information System in Improving the Quality of Regional Financial Reports - Wahyu Setyawan (Dhana, 2025)
This study aims to evaluate the effectiveness of the implementation of the Government Accounting Information System (SIAP) in improving the quality of regional financial reports, with a focus on the Regional Government in Lampung Province. In the context of bureaucratic reform and demands for public transparency, SIAP is expected to be a strategic instrument that not only supports administrative compliance, but also strengthens fiscal accountability through the presentation of real-time and integrated data. This study uses a descriptive qualitative approach, with data collection techniques in the form of in-depth interviews and documentation. The results of the study indicate that SIAP contributes to increasing the accuracy and timeliness of reporting, as well as strengthening the internal oversight function. However, the implementation of SIAP still faces various obstacles, including weak digital literacy of human resources, lack of system integration, and low institutional commitment in several regions. The effectiveness of SIAP depends not only on technological sophistication, but also on organizational readiness, leadership quality, and regulatory alignment. This study emphasizes that the success of SIAP requires a holistic approach based on synergy between systems, people, and institutional structures. Thus, SIAP will be able to act as a foundation for transparent, accountable, and data-based regional financial governance, not just an administrative reporting tool.